2013
DOI: 10.1242/jcs.134122
|View full text |Cite
|
Sign up to set email alerts
|

Distinct modes of centromere protein dynamics during cell cycle progression in Drosophila S2R+ cells

Abstract: SummaryCentromeres are specified epigenetically in animal cells. Therefore, faithful chromosome inheritance requires accurate maintenance of epigenetic centromere marks during progression through the cell cycle. Clarification of the mechanisms that control centromere protein behavior during the cell cycle should profit from the relatively simple protein composition of Drosophila centromeres. Thus we have analyzed the dynamics of the three key players Cid/Cenp-A, Cenp-C and Cal1 in S2R+ cells using quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 83 publications
2
51
0
Order By: Relevance
“…Although plasmid supercoiling assay previously demonstrated that the subregion (1-160) of CAL1 lacking the self-association domain is sufficient for dCENP-A nucleosome assembly activity in vitro , excess of dCENP-A/H4/CAL1 complex under these conditions might be sufficient to overcome the self-association requirement observed in vivo. A role for dCENP-C as a stable platform for CAL1/dCENP-A recruitment is further supported by experiments indicating that dCENP-C is stably bound to centromeres (Lidsky et al, 2013;Mellone et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although plasmid supercoiling assay previously demonstrated that the subregion (1-160) of CAL1 lacking the self-association domain is sufficient for dCENP-A nucleosome assembly activity in vitro , excess of dCENP-A/H4/CAL1 complex under these conditions might be sufficient to overcome the self-association requirement observed in vivo. A role for dCENP-C as a stable platform for CAL1/dCENP-A recruitment is further supported by experiments indicating that dCENP-C is stably bound to centromeres (Lidsky et al, 2013;Mellone et al, 2011).…”
Section: Discussionmentioning
confidence: 78%
“…To ensure epigenetic inheritance the centromere mark must stably persist through the multiple division cycles of a cell. Unlike canonical histone H3, CENP-A nucleosomes are not replenished during DNA replication but from late mitosis through G1 phase (Dunleavy et al, 2012;Jansen et al, 2007;Lidsky et al, 2013;Schuh et al, 2007). One attractive model for the self-propagation of CENP-A is an epigenetic loop, where one or more adaptors recognize and direct the deposition of new CENP-A.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CAL1 also interacts with the highly conserved FACT complex (Chen et al, 2015) and localizes to the nucleolus (Chen et al, 2012; Lidsky et al, 2013). We hypothesize that the overall CAL1 sequence is under purifying selection (Phansalkar et al, 2012) to preserve its functional interactions with highly conserved partners, while key residues within the N terminus of CAL1 evolve to maintain the functional interaction with CENP-A.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike canonical chromatin maintenance, centromeric chromatin maintenance is decoupled from DNA replication. As a result, CENP-A levels on the sister chromatids are reduced by half during replication (Jansen et al, 2007;Hemmerich et al, 2008;Dunleavy et al, 2009;Mellone et al, 2011;Lidsky et al, 2013). To ensure stable centromere maintenance, CENP-A nucleosomes must return to their original levels through active CENP-A deposition.…”
Section: Introductionmentioning
confidence: 99%